China in the World : Culture, Politics, and World Vision. - Wang, Ban. (Durham : Duke University Press, 2022)
Ban Wang traces the shifting concept of the Chinese state from the late nineteenth century to the present, showing how the Confucian notion of tianxia--"all under heaven"--influences China's dedication to contributing to and exchanging with a common world.
Cover -- Contents -- Series Editor's Foreword -- Acknowledgments -- Introduction: Empire, Nation, and World Vision -- 1. Morality and Global Vision in Kang Youwei's World Community -- 2. Nationalism, Moral Reform, and Tianxia in Liang Qichao -- 3. World Literature in the Mountains -- 4. Art, Politics, and Internationalism in Korean War Films -- 5. National Unity, Ethnicity, and Socialist Utopia in Five Golden Flowers -- 6. The Third World, Alternative Development, and Global Maoism -- 7. The Cold War, Depoliticization, and China in the American Classroom -- 8. Using the Past to Understand the Present -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books